Participation and performance trends in ‘Ultraman Hawaii’ from 1983 to 2012 - Meili, Dimirela (BioMed Central, 2013)
BACKGROUND: Participation and performance trends have been investigated in a single stage Ironman triathlon such as the ‘Ironman Hawaii,’ but not for a multi-stage ultra-triathlon such as the ‘Ultraman Hawaii’ covering a total distance of 515 km. The aims of this study were to analyze (1) changes in participation and performance, (2) sex-related differences in overall and split time performances, and (3) the age of peak performance in Ultraman Hawaii. METHODS: Age and race times including split times for 98 women and 570 men who successfully finished Ultraman Hawaii (day 1 with 10-km swimming and 145-km cycling, day 2 with 276-km cycling, and day 3 with 84-km running) between 1983 and 2012 were analyzed. Changes in variables over time of annual winners and annual top three women and men were investigated using simple linear regression analyses. RESULTS: The number of female finishers increased (r(2) = 0.26, p < 0.01), while the number of male finishers remained stable (r(2) = 0.03, p > 0.05). Overall race times decreased for both female (r(2) = 0.28, p < 0.01) and male (r(2) = 0.14, p < 0.05) winners and for both the annual top three women (r(2) = 0.36, p < 0.01) and men (r(2) = 0.14, p = 0.02). The sex difference in performance decreased over time from 24.3% to 11.5% (r(2) = 0.39, p < 0.01). For the split disciplines, the time performance in cycling on day 1 (r(2) = 0.20, p < 0.01) and day 2 decreased significantly for men (r(2) = 0.41, p < 0.01) but for women only on day 2 (r(2) = 0.45, p < 0.01). Split times showed no changes in swimming and running. The age of the annual winners increased from 28 to 47 years for men (r(2) = 0.35, p < 0.01) while it remained stable at 32 ± 6 years for women (r(2) < 0.01, p > 0.05). The age of the annual top three finishers increased from 33 ± 6 years to 48 ± 3 years for men (p < 0.01) and from 29 ± 7 years to 49 ± 2 years for women (p < 0.01). CONCLUSIONS: Both the annual top three women and men improved performance in Ultraman Hawaii during the 1983–2012 period although the age of the annual top three women and men increased. The sex-related difference in performance decreased over time to reach approximately 12% similar to the reports of other endurance and ultra-endurance events. Further investigations are required to better understand the limiting factors of the multi-activities ultra-endurance events taking place over several days.